The Perceptions Of IT Employees Towards IT Outsourcing In Malaysia - Abdullah, Mohd Radi (2005)
This paper will initially try to understand the theoretical model behind outsourcing. The researcher would like to find out which IT sourcing strategy is the best strategy from IT employees' perspective.